Growing arugula plants using aeroponic culture with an automated irrigation system - Ríos Salazar, Jhon D.; Candelo-Becerra, John E.; Hoyos Velasco, Fredy E. (International Journal of Agricultural and Biological Engineering, 2020)
The paper presents an efficient form of growing arugula plants by means of automatic control of an aeroponic culture irrigation system. The system considers a reprogrammable electronic circuit that uses software to generate different irrigation cycles to obtain an adequate growth of arugula crops. Results show how different samples grown in a greenhouse had the same growth behavior as field-grown samples during the test period. It was possible to obtain a more efficient and sustained five-week production to supply consumers by having a continuous cycle irrigation system, which was operated for 35 d. The growth and number of leaves were maintained in a similar way for different plants analyzed. Roots grow similarly, but some of them showed size differences during the five weeks.Keywords: aeroponic culture, arugula plants, food production, irrigation systems, smart systemDOI: 10.25165/j.ijabe.20201303.5194Citation: Ríos Salazar J D, Candelo-Becerra J E, Hoyos Velasco F E. Growing arugula plants using aeroponic culture with an automated irrigation system. Int J Agric & Biol Eng, 2020; 13(3): 52–56.